Acute Anterior Cruciate Ligament Rupture: Repair or Reconstruction? Five-Year Results of a Randomized Controlled Clinical Trial. Issue 7 (June 2022) - Hoogeslag, Roy A.G.; Huis In 't Veld, Rianne; Brouwer, Reinoud W.; de Graaff, Feike; Verdonschot, Nico
Background: High-level evidence for short–term outcomes of contemporary anterior cruciate ligament (ACL) suture repair (ACLSR) in comparison with those of ACL reconstruction (ACLR) is scarce. High-level evidence for mid- and long–term results is lacking, whereas outcomes of ACLSR in several historical studies were shown to deteriorate at midterm follow–up after initial good short–term outcomes. Hypothesis: Contemporary ACLSR is noninferior to ACLR in the treatment of acute ACL rupture in terms of patient self–reported outcomes at 5 years postoperatively. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 48 patients were enrolled in the study and, after stratification and randomization, underwent either dynamic augmented (DA) ACLSR or anatomic single–bundle ACLR. The primary outcome measure was the International Knee Documentation Committee 2000 (IKDC) subjective score (IKDCs). Furthermore, the Knee injury and Osteoarthritis Outcome Score (KOOS), Tegner Activity Scale score (TAS), visual analog scale score for satisfaction (VASs), IKDC physical examination score (IKDCpe), limb symmetry index for quadriceps (LSIq) and hamstrings (LSIh) strength and jump test battery (LSIj), Kellgren-Lawrence grade of osteoarthritis (OA), and rate of adverse events were recorded. Analyses were based on an intention–to–treat principle. Results: The lower limit of the 2–sided 95% CI for the median IKDCs of the DA ACLSR group (n = 23; 75.9) was lower than the prespecified noninferiority margin (n = 21; 86.6). Therefore, the null hypothesis was rejected. However, the upper limit of the 2–sided 95% CI of the DA ACLSR group (100.0) was higher than the median IKDCs of the ACLR group (96.6), rendering the result for noninferiority inconclusive. No statistical difference was found between groups for median IKDCs (repair, 90.2; reconstruction, 96.6). Furthermore, no statistically significant differences were found for any of the secondary outcome measures for the DA ACLSR compared with the ACLR group: KOOS Symptoms, 92.9 versus 96.4; KOOS Pain, 100 versus 97.2; KOOS Activities of Daily Living, 100 versus 100; KOOS Sport and Recreation, 85.0 versus 100; TAS score, 7.0 versus 6.5; VASs, 9.2 versus 8.7; IKDCpe, 81.8% versus 100%; LSIq, ≥91.6 versus ≥88.2; LSIh, ≥95.1 versus ≥90.7; LSIj, ≥94.2 versus ≥97.6; OA grade 0, 90.9% versus 77.8%; clinical ACL failure rate, 20.8% versus 27.2%; and repeat surgery rate, 37.5% versus 20.0%, respectively. Conclusion: It remains inconclusive whether the effectiveness of DA ACLSR is noninferior to that of ACLR in terms of subjective patient–reported outcomes as measured using the IKDCs. Although DA ACLSR may be a viable treatment option for patients with acute ACL rupture, caution must be exercised when considering this treatment for young, active patients, corresponding to the present study population.